PENGARUH KUALITAS PELAYANAN DAN FASILITAS FOOD AND BEVERAGE SERVICE DEPARTMENT TERHADAP KEPUASAN TAMU DI SINTESA PENINSULA HOTEL MANADO - Marthen R. Tombeg; Sony Wijanarko (Jurnal Hospitaliti, 2024)
This research aims to find out the influence of service quality and facilities food and beverage service department on guest satisfaction at Sintesa Peninsula Hotel Manado. The research method used is the Quantitative Method, with Multiple Linear Regression data analysis techniques. The population in this study were hotel guests, with a sample of 30 guests at Sintesa Peninsula Hotel Manado. The research results prove that Service Quality and Facilities have a positive and significant effect on Guest Satisfaction with a regression coefficient value of 3,225 and a significance of 0.000. This shows that the higher the Employee Service Quality, the higher the Guest Satisfaction. Facilities have a positive and significant effect on guest satisfaction with a regression coefficient value of 8.738. This shows that the better the facilities available at the hotel, the better guest satisfaction will be. Quality of Service and Facilities has a significant influence on Guest Satisfaction with an F-value of 161.471 and a significance of 0.000. This shows that the better the quality of service and facilities, the more guest satisfaction will increase. The conclusion of this research is that the quality of service and facilities has a significant influence on guest satisfaction at Sintesa Peninsula Hotel Manado. Suggestions given by Sintesa Peninsula Hotel Manado, especially in the food and beverage service department, maintain or further improve the high quality of service regarding guest satisfaction that has been provided, and always updating facilities and adding staff to the food and beverage service department.